Implementation of the indoor navigation algorithm based on bluetooth low energy 4.0. technology - Овсянников, Александр Александрович; Новиков, Павел Андреевич (Computer Tools in Education, 2015)
Some of the indoor-navigation implementational wireless models are described in this article. Algorythms, based on basic models, are proposed. Based on data from the beacons the impact of other wireless connections is analyzed.
Keywords: mobile technology; wireless technology; navigation algorythms; artificial neural network